Urinary incontinence persisting after childbirth: extent, delivery history, and effects in a 12–year longitudinal cohort study. (2nd April 2015) - MacArthur, C; Wilson, D; Herbison, P; Lancashire, RJ; Hagen, S; Toozs‐Hobson, P; Dean, N; Glazener, C; ,
Abstract : Objective: To investigate the extent of persistent urinary incontinence (UI) 12 years after birth, and association with delivery‐mode history and other factors. Design: Twelve‐year longitudinal cohort study. Setting: Maternity units in Aberdeen, Birmingham, and Dunedin. Population: Women who returned questionnaires 3 months and 12 years after index birth. Methods: Data on all births over a period of 12 months were obtained from the units and then women were contacted by post. Main outcome measure: Persistent UI reported at 12 years, with one or more previous contact. Results: Of 7879 women recruited at 3 months, 3763 (48%) responded at 12 years, with 2944 also having responded at 6 years; non‐responders had similar obstetric characteristics. The prevalence of persistent UI was 37.9% (1429/3763). Among those who had reported UI at 3 months, 76.4% reported it at 12 years. Women with persistent UI had lower SF12 quality of life scores. Compared with having only spontaneous vaginal deliveries (SVDs), women who delivered exclusively by caesarean section were less likely to have persistent UI (odds ratio, OR 0.42, 95% CI 0.33–0.54). This was not the case in women who had a combination of caesarean section and SVD births (OR 1.01, 95% CI 0.78–1.30). Older age at first birth, greater parity, and overweight/obesity were associated with persistent UI. Of 54 index primiparae with UI before pregnancy, 46 (85.2%) had persistent UI. Conclusions: This study, demonstrating that UI persists to 12 years in about three‐quarters of women, and that risk was only reduced with caesarean section if women had no other delivery mode, has practice implications. Tweetable abstract: A longitudinal study of 3763 women showed a prevalence of persistent UI 12 years after birth of 37.9%. Tweetable abstract: A longitudinal study of 3763 women showed a prevalence of persistent UI 12 years after birth of 37.9%.